2021
DOI: 10.1007/s11869-021-00978-z
|View full text |Cite
|
Sign up to set email alerts
|

Biological contaminants in the indoor air environment and their impacts on human health

Abstract: Indoor air environment contains a complex mixture of biological contaminants such as bacteria, fungi, viruses, algae, insects, and their by-products such as endotoxins, mycotoxins, volatile organic compounds, etc. Biological contaminants have been categorized according to whether they are allergenic, infectious, capable of inducing toxic or inflammatory responses in human beings. At present, there is a lack of awareness about biological contamination in the indoor environment and their potential sources for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 53 publications
0
38
0
Order By: Relevance
“…Aspergillus infections mostly affect the respiratory system. Inhaled Aspergillus spores can germinate in the presence of ideal lung conditions such as high humidity, oxygen, and carbon dioxide [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aspergillus infections mostly affect the respiratory system. Inhaled Aspergillus spores can germinate in the presence of ideal lung conditions such as high humidity, oxygen, and carbon dioxide [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Findings of the pilot study conducted in Finland to assess the indoor air problems which revealed the irritated, stuffy, or runny nose (20%), itching, burning, or irritation of the eyes (17%), and fatigue (16%) found the most common symptoms in the workers. Women had a higher proportion of indoor air problems than men, indicating the importance of the current study [12].…”
Section: Plos Onementioning
confidence: 74%
“…Sources of these microorganisms in indoor air may include people, organic dust, storage of various products, and circulation of air through natural and artificial ventilation systems [7] According to a previous study, roughly 30% of office workers suffer from ailments due to poor indoor air quality [8]. Exposure to these contaminants may cause allergic reactions, infections, intoxication, and various molecular reactions [6,[9][10][11][12][13]. The importance of airborne microorganisms on health was highlighted by the World Health Organization (WHO) [14].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the bacterial load being attributed to the number of occupants as a human is a reservoir of S. aureus 31 when they are released by different occasional activities like sneezing, coughing, and talking. 12 , 13 However, the number of occupants by itself cannot affect microbial load in the indoor environment. Rather the crowding index matter.…”
Section: Discussionmentioning
confidence: 99%
“…may also contribute to poor IAQ. 3 , 5 , 7 , 10 Bacteria, fungi, and viruses, collectively microorganisms 11 , 12 are the key elements of indoor air pollutants and contribute about 5% to 34% to indoor air pollution health problems. 3 , 5 , 8 , 9 Particular activities like talking, sneezing, coughing, walking, and washing can majorly release these airborne biological contaminants and form air suspensions that increase exposure for the inmates.…”
Section: Introductionmentioning
confidence: 99%